The grain trade and the failure of international control - Nick Butler (Intereconomics, 1983)
In common with international agricultural trade in general the grain trade has remained immune to pressure for liberalization, and equally immune to suggestions of international management in the form of reserve stock holding, price floors and ceilings, or a full scale commodity agreement. What are the reasons for failure of such attempts in the past? Is there still a chance for GATT at least to minimize the adverse effects, especially on developing countries, of the present inefficient trading system?
Keywords: 330; Agricultural Policy